Successful treatment of malignant pheochromocytoma with sacrum metastases: A case report. Issue 35 (August 2018) - Liu, Shuzhong; Zhou, Xi; Song, An; Li, William A.; Rastogi, Radhika; Wang, Yipeng; Liu, Yong
Abstract: Rationale: Malignant pheochromocytoma in the spine is a rare disease without standard curative managements so far. The objective of this article is to report a very rare case of malignant pheochromocytoma with sacrum metastases causing severe lumbosacral pain, which was presented with acute radiculopathy and treated with three operations combined with cement augmentation and stabilization. The management of these unique cases has yet to be well-documented. Patient concerns: A 58-year-old man presented with lumbosacral pain, radiating pain and numbness of the right extremity. The patient underwent excision of right adrenal pheochromocytoma in 2010. Imaging studies revealed the density of soft tissues, obvious bony destruction in the sacrum, and significant spinal cord obstruction. Diagnoses: We believe this is the first report of malignant pheochromocytoma with sacrum metastases. Interventions: The patient underwent tissue biopsy and osteoplasty after embolization of the internal iliac artery in January 2015, and exploratory surgery, circumferential spinal cord decompression, and a stabilization procedure via a posterior approach in June 2015 due to spinal canal stenosis caused by cement. Since the position of pedicle screw was not good enough, a revision surgery was performed the next day following the procedures in June 2015. Outcomes: The patient's neurological deficits improved significantly after the third surgery, and the postoperative period was uneventful at the three-year follow-up visit. Lessons: We recommend the posterior approach for spinal decompression of the metastatic pheochromocytoma when the tumor has caused neurological deficits. Osteoplasty by cement augmentation is also a good choice for surgical treatment. However, the potential risk of complications in bone cement applications need to be fully recognized.